2021
DOI: 10.5539/elt.v14n5p109
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Study on Teachers’ Feedback in EFL Classroom in China

Abstract: EFL classroom teaching in China, no matter whether it is traditional one or a flipped one, is a dynamic communicative process by using English with the aim of learning it. The interactive discourse between the teacher and the student has its own pragmatic functions, especially the feedback given by the teachers which may influence the teaching and learning efficiency. In order to provide appropriate investigation resources, a corpus of 128,223 words with 36.65 hour-2199 minute real audiovisual college EFL clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
(15 reference statements)
1
7
0
Order By: Relevance
“…The described classroom observations of the teachers in the field indicated that they did not give enough positive feedback on the students' correct speech and thus limited potential learning outcomes for them. This conclusion is in consonance with that of Liu, Liu, and Zhang (2021), who found that general supportive feedback can greatly facilitate the interaction between teachers and students, since it is capable of not only expressing participation, acceptance, and recognition, but also implying that the conversational turn has yet to be finished, thus encouraging the student to continue speaking.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The described classroom observations of the teachers in the field indicated that they did not give enough positive feedback on the students' correct speech and thus limited potential learning outcomes for them. This conclusion is in consonance with that of Liu, Liu, and Zhang (2021), who found that general supportive feedback can greatly facilitate the interaction between teachers and students, since it is capable of not only expressing participation, acceptance, and recognition, but also implying that the conversational turn has yet to be finished, thus encouraging the student to continue speaking.…”
Section: Discussionsupporting
confidence: 87%
“…The results of Liu, Liu, & Zhang (2021) show that though general supportive feedback discourse in the classroom accounts for a small proportion of all positive feedback, it promotes the interaction between teachers and students to a large extent. General supportive feedback usually uses interjections, such as "Yeah", "Um", "Uhhuh", which have no exact meanings but implicit pragmatic meanings, demonstrating teachers' approval, satisfaction, or doubt.…”
Section: Literature Review Positive Feedback In Language Learningmentioning
confidence: 92%
See 1 more Smart Citation
“…Despite the wide use of Conversation Analysis in psychotherapy and pragmatic linguistics research, it is almost impossible to find studies that would capture the problem of ageing and age-related social changes (Liu et al, 2021 ; Yoon and Stine-Morrow, 2019 ; Yu and Liang, 2018 ). The present study seeks to narrow this gap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, Conversation Analysis was applied to examine the role of the rapid ageing process in the changing labour market. Technological advancement changes the labour market, imposing new requirements on educational backgrounds and redefining the linguistic experience of social subjects (Liu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%